Influence of socio-psychological and external factors on residents’ willingness to participate in sustainable solid waste handling practice in Dammam, Saudi Arabia - Hendawy, Ossama Ahmed Labib Ibrahim (2021)
Although the main problem in Dammam city is an increasing of solid waste production without treatment except landfilling and lack of waste segregation greatly affects the residents’ handling practices of solid waste due to incorrect disposing practice. This study allows the residents of Dammam are able to participate in sorting and recycling of sustainable solid waste. The objective of this study explored the possibility of Dammam residents’ participation in sorting and recycling through comparing the sustainable waste handling practice from different income level groups according to family income levels, to determine the impacts of independent variables on the willingness of residents to participate in sustainable waste handling practices and examine the moderating effects of demographic factors such as gender and income level on residents’ willingness to participate in sustainable handling practices in Dammam. The number of respondents was 450 from 75 different districts in Dammam City. Through objective 1 there was statistically significant difference between low and high levels household Dammam City in awareness and perceived behaviour control in willingness in waste sorting and recycling but with middle level there was only significance different in perceived behaviour control also, there was statistically significant difference between high and middle levels in government facilitators in their willingness to sort and recycle waste in Dammam City. The attitude scored highly percentage was 57.1% in waste sorting and 248 55.1% in waste recycling were in the high level of attitude towards waste recycling. The awareness scored 46.9% in sorting and 47.1 % in recycling in the high level. In perceived behaviour control scored 47.8% in sorting while it scored 49.6% in recycling were in the middle level. In market incentives scored 44.2% and social influences scored 51.1% were in the high level. Through objective 2 in attitude the correlation coefficient was strong significant 0.731 while in awareness the correlation coefficient was middle significant 0.322. The correlation coefficient in PCB was weak significant 0.25 while in market incentives and governmental facilitators, the correlation coefficients were 0.556 and 0.604 respectively and finally, The correlation in social influences the correlation coefficient was 0.344 it was middle significant. The structural equation model analysis indicated that the model accounted for 67% of the variance in willingness to sort and recycle waste. This suggests that the model has an acceptable explanatory power. In objective 3 the moderating analysis revealed that the causal relationships between attitude willingness to sort and recycle low income β = 0.3497, p = 0.000 and high income β = -0.1044, p = 0.3638, market incentive willingness to sort and recycle low income β = 0.0439, p = 0.0142 and high income β = 0.2583, p = 0.0766, and government facilitators willingness to sort and recycle low income β = 0.0451, p = 0.26006 and high income β = 0.4634, p = 0.0012 were moderated by income level. The moderating analysis for gender revealed that the causal associations between market incentive willingness to sort and recycle male β = 0.084, p = 0.028 and female β = 0.418, p = 0.129, and social influence willingness to sort and recycle male β = -0.178, p = 0.000 and female β = 0.708, p = 0.041, were moderated by gender.